The Containment of Heritage: Setting Limits to the Growth of Heritage in Ireland - Cooke, Patrick (Trinity College Dublin, 2003)
The Containment of Heritage: Setting Limits to the Growth of Heritage in Ireland examines the expansionary pressures at work within the field of heritage in Ireland. The last twenty years have witnessed an unprecedented expansion in the designation and protection of built and natural heritage in Ireland. This paper suggests that the gap between our aspirations for the protection of heritage and the resources to fulfill them may become unsustainable unless a policy framework is devised to ensure that heritage costs are properly evaluated, and measures put in place to ensure that heritage growth is containable and manageable. The paper argues that a containment strategy for heritage requires a broad framework that takes conceptual, economic, administrative and socio-political factors into account. The paper proposes that the real economic costs of heritage should be clarified and that more rigorous classification systems are needed to control its expansion. The author argues that the state?s burden of heritage management should be shared to a far greater extent by voluntary and local bodies and that the National Museum should be disburdened of the responsibility of caring for the bulk of archaeological finds through the setting up of a ?National Archaeological Repository?.
Keywords: Public Policy; Heritage; Ireland